Optimum conditions determination of methyl methacrylate obtaining over tungsten-containing catalyst - Dmytruk, Yuliia; Ivasiv, Volodymyr; Nebesnyi, Roman; Maykova, Svitlana (Eastern-European Journal of Enterprise Technologies, 2015)
The main common methods of methyl methacrylate producing are acetoncyanohydrin method and oxidation of isobutylene and tert-butanol. Because of the significant drawbacks of these methods, it is important to develop new, alternative ways of methyl methacrylate obtaining, one of which could be aldol condensation of methyl propionate with formaldehyde in the gas phase. The actual task for today is to find out effective catalysts for this process. For this aim, methyl propionate condensation with formaldehyde was studied in the presence of B2O3-P2O5-WO3/SiO2 catalyst, which previously has showed high activity in the condensation of propionic acid with formaldehyde to methacrylic acid. The paper also investigates the influence of methanol on the side reaction of methyl propionate hydrolysis; it was found that adding methanol causes a slight increase in MMA selectivity, but the yield of unsaturated products decreases, and therefore adding methanol to the reaction mixture for the MP condensation with FA over B2O3-P2O5-WO3/SiO2 catalyst is impractical. The optimum conditions for MP condensation with FA, namely temperature 653 K and contact time 12 s were found. Under these conditions, in the presence of B2O3-P2O5-WO3/SiO2 catalyst with an atomic ratio of components B:P:W 3:1:0.6 respectively total yield of MMA and MAA was 31.91% while their total selectivity was 32.3%.